Detection and Comparison of 10 Metals in Brachymystax Lenok from the Genhe River and Ussuri River - Wang, Haitao; Mou, Zhenbo (Asian Journal of Chemistry, 2011)
Assessment on heavy metals pollution of aquatic products has been paid more and more attention. Brachymystax lenok from Genhe river and Ussuri river of northeastern China were detected the contents of heavy metals to evaluate its safety. The results proved that the detecting method in these conditions is accurate and precise. Brachymystax lenok muscle contains many kinds of mineral elements, Cu, Pb, Zn, Cr, Fe, Ca, Na and Mn, but contents of harmful elements are very low, so Brachymystax lenok from both rivers are safe in terms of heavy metals. Compared with Brachymystax lenok from Ussuri river, Brachymystax lenok from Genhe river contains more Cu, Pb, Zn, Cr Fe and Ca and less Na and Mn, which should be relative to water environment, so we should control the river water environment.